DC Power System of Electric Vehicle - Zhang Liwei; Wang Xiao; Zhang Yujin (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In recent years, environmental and energy problem has become one of the world's hot spot problems. Today, the road cars not only consume a lot of oil resource, but also cause serious pollution to human survival environment. Therefore, to save energy and protect environment, a green environmental friendly electric car instead of fuel car will be needed for sustainable development of the society. Electric vehicle has no pollution, low noise, high efficiency, diversification, simple structure and convenient maintaining; the development of green cleaning electric vehicle is the trend, and the inevitable choice. The power supply system of electric vehicle can be divided into three parts, the battery charging system, motor drive system and dc load power supply system. This paper mainly studies the dc load power supply system. Main function is to convert the high-voltage of the battery in the electric vehicle into low voltage output, provide the power supply for the low voltage dc load, including the car safety system, windshield wiper system, audio system. On the basis of the analysis of the parameters, this article designs the converter, sets up the principle prototype, analyzes the experimental results and finally makes conclusion. The vehicle power supply is green, environment friendly, high-efficiency, digital and intelligent.  DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3511